The ecology and physiology of the springhare (Pedetes capensis) in the Eastern Cape Province of South Africa - Peinke, Dean Michael (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2001)
Springhare are large, bipedal, nocturnal, herbivorous, burrowing rodents that are found in arid and semi-arid parts of southern and eastern Africa. In this thesis I examine the general ecology, biology and physiology of these animals in the Eastern Cape Province of South Africa. An investigation of their distribution and activity in the study site showed that springhare exhibit a preference for flat, open, recently disturbed habitat that is dominated by the grass Cynodon dactylon and the sedge Cyperus esculentus. These two species constitute a major proportion of their diet. The impact of spring hare on chicory and grazing is also discussed. Nightly activity generally peaks soon after dark and decreases in the 2-4 hour period before sunrise. This pattern is, however, modified by moonlight. Springhare typically respond to moonlight by reducing aboveground activity, shifting their activity to dark moonless periods of the night, and by reducing their use of open space. Contrary to earlier reports, springhare utilise several different burrow systems spread over large areas. They regularly change burrow systems and seldom spend more than a few consecutive days in each. Springhare do not appear to defend territories but recently used burrows appear to be avoided by conspecifics. Males and females on average use a similar number of burrows, scattered over similar sized areas. Burrows are shown to provide a stable microclimate of moderate temperature and high humidity throughout the year. Reproduction is continuous and there is no synchronised breeding season. The ability to reproduce throughout the year is attributed primarily to their ability to utilise subterranean food stores. The overall reproductive strategy of springhare (a single young with long gestation and weaning) is unusual for a mammal of this size but may be linked to low levels of adult and juvenile mortality. Physiologically, springhare are reasonably well adapted to life in hot, arid environments. They produce a concentrated urine, exhibit a high tolerance to dehydration, are good osmoregulators capable of maintaining plasma volume, osmolality and ion balance over long periods of water deprivation, and are able to produce dry faeces. They are also good thermoregulators at low ambient temperatures, which are usually encountered at night, but are poor thermoregulators at high ambient temperatures, which they avoid behaviourally.
Keywords: Hares -- South Africa -- Eastern Cape; Hares -- Breeding -- South Africa -- Eastern Cape; Hares -- Ecology -- South Africa -- Eastern Cape; Hares -- Physiology